Civic Ecology Uplifts Low-Income Communities, Improves Ecosystem Services and Well-Being, and Strengthens Social Cohesion - (:unkn) unknown (My University, 2021)
Ecosystem services enhance well-being and the livelihoods of disadvantaged communities. Civic ecology can enhance social-ecological systems; however, their contributions to ecosystem services are rarely measured. We analysed the outcomes of civic ecology interventions undertaken in Durban, South Africa, as part of the Wise Wayz Water Care programme (the case study). Using mixed methods (household and beneficiary (community members implementing interventions) surveys, interviews, field observations, and workshops), we identified ecosystem service use and values, as well as the benefits of six interventions (solid waste management and removal from aquatic and terrestrial areas, recycling, invasive alien plant control, river water quality monitoring, vegetable production, and community engagement). Ecosystem services were widely used for agriculture, subsistence, and cultural uses. River water was used for crop irrigation, livestock, and recreation. Respondents noted numerous improvements to natural habitats: decrease in invasive alien plants, less pollution, improved condition of wetlands, and increased production of diverse vegetables. Improved habitats were linked to enhanced ecosystem services: clean water, agricultural production, harvesting of wood, and increased cultural and spiritual activities. Key social benefits were increased social cohesion, education, and new business opportunities. We highlight that local communities can leverage natural capital for well-being and encourage policy support of civic ecology initiatives.
Keywords: African Research